Determinan Balita Stunting di Kabupaten Landak, Kalimantan Barat: Studi Potong Lintang: The Stunting Determinants in Toddlers from Landak Regency, West Kalimantan: A Cross-Sectional Study - Trisnawati, Elly; Widyastutik, Otik; Suryadi, Edy; Alamsyah, Dedi; Budiastutik, Indah; Ruhama', Ufi (Universitas Airlangga, 2024)
Background: Stunting is a nutrition problem that can slow down the growth. With prevalence at 32.5%, Landak Regency in West Kalimantan has been designated as a stunting hotspot. The lack of a maximum penalty for the stunting case in Landak Regency is not based on factors causing the stunting itself, because there is no identifiable factor causing the stunting in certain area due to narrow roads and sharp curves. Objectives: The objective of this study was to identify causes and distribution of the stunting case in Landak Regency. Methods: A total of 330 households in Meranti, Sebangki, and Senakin were included in this cross-sectional study because they were at a risk of the stunting. Toddlers, mothers, health care, and environmental factors were among the found variables. The researchers employed a basic random sampling strategy for the sampling and used the secondary health center data to find out whether or not toddlers were stunted. Researchers in this study collected data on the independent variables by observing and interviewing participants. Using the chi-square test, the data was analyzed. Results: The results showed that determinants of the stunting in Landak Regency were the history of early breastfeeding initiation (p-value=0.032), exclusive breastfeeding (p-value=0.042), frequency of exclusive breastfeeding (p-value=0.040), the continued breastfeeding (p-value=0.024), complementary feeding (p-value=0.042), immunization history (p-value=0.007), infectious disease history (p-value=0.000), maternal height (p-value=0.046), delivery assistance (p-value=0.000), access to health services (p-value=0.004), the role of health workers (p-value=0.002), and family latrine ownership (p-value=0.000). Conclusions: Several factors were found to be associated with incidence of the stunting among toddlers in Landak Regency.